Gothic Romance Dalam Light Novel Owari no Seraph: Ichinose Guren 16 Sai no Hametsu Karya Kagami Takaya - Nadia Wirda Ummah; Heri Widodo (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2022)
The light novel Owari no Seraph: Ichinose Guren 16 sai no Hametsu is a light novel that has attracted a lot of readers' interest, thus becoming the 10th best-selling light novel. This light novel has also been adapted into various forms, including drama CDs and drama musicals. This light novel, which is intended for young male readers, is categorized as having the genres of action, fantasy, romance, and school life. However, this novel has the main element of the story with a gothic romance formula with Pamela's narrative pattern. The heroin figure is described as a strong figure and ready to do anything, even being able to do anything as long as everything he does can make him unite with the hero. The action, adventure, and fantasy that exist are narratives that strengthen the love relationship between hero and heroine.